Analysis of Difficulties and Countermeasures in Inventory Supervision and Counting of Fresh Produce Industry - Feng, Huixin (Exploring Science Academic Conference Series, 2026)
With the rapid development of the fresh food industry, the characteristics of its inventory, such as perishability, short shelf life, and dynamic value decay, pose severe challenges to the traditional inventory count supervision procedures. This paper systematically analyzes the core difficulties in the inventory count supervision of the fresh food industry regarding quantity accuracy, quality assessment, timeliness, and weak internal controls within enterprises, pointing out that the contradiction between static supervision and dynamic inventory is the root cause of the problem. On this basis, it proposes constructing a trinity countermeasure system of , technology empowerment, strategy innovation, institutional guarantee, : achieving dynamic supervision and real-time valuation through Internet of Things (IoT), big data, and AI technologies; formulating differentiated supervision strategies, such as prioritizing the counting of perishable items and weighing frozen products after de-icing; and promoting the industry to issue the , Guidelines for Inventory Management and Supervision in the Fresh Food Industry, to standardize the entire chain’s internal control processes. This research aims to provide theoretical support and practical references for improving the effectiveness of inventory count supervision in the fresh food industry and reducing audit risks.